Peran Vitamin D dalam Proses Penyakit Diabetes Mellitus (Journal of Telenursing (JOTING), 2025)
This study endeavors to elucidate the role of vitamin D in the pathogenesis of diabetes mellitus through a systematic review, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The Joanna Briggs Institute (JBI) critical appraisal tools were employed to evaluate the methodological quality of the included studies. Data sources encompassed Scopus, PubMed, and Google Scholar databases. The findings underscore the potential of vitamin D supplementation to enhance glycemic regulation and mitigate the risk of diabetes onset. Moreover, vitamin D is implicated in calcium and phosphorus homeostasis and exerts influence over pancreatic β-cell function, immune modulation, and the progression of diabetes-related complications. Hypovitaminosis D has been associated with increased insulin resistance, impaired glycemic control, and elevated susceptibility to both type 1 and type 2 diabetes. In conclusion, vitamin D functions as an immunomodulatory agent that not only contributes to the prevention of diabetes mellitus but also attenuates its progression by enhancing insulin secretion, alleviating oxidative stress, reducing insulin resistance, and modulating iron metabolism. Keywords: Diabetes Mellitus, Disease Process, Supplement, Vitamin D